EVALUATIONS OF PROGRAMS IN HEALTH PROMOTION: REFLECTIONS AND PERSPECTIVES FOR THE PHYSICAL EDUCATION IN OLD AGE. (Fiep Bulletin - online, 2014)
In The physical education is increasing the number of implantation on initiatives with the proposal to promote the physical education practice for old aged. However, most part of the intervention programs for the aged people is created based on epistemological models, which characterize the group based on the prevalence or universal incidence and generalized of determiners of diseases considered as characteristics of this fase of life, being that, guided by the biomedical model rules. Besides, it predominates on the implantation and working of the programs a verticalized pattern and tax. Then, the objective of this work is to discuss and think of the evaluation of the physical education programs for old aged under the health promotion. The theorical reference pointed some directions towards the programs evaluation discussed  on the Health promotion; the aged person must act  in a participative  and critic way on the programs evaluation; a previous analyze on the several aspects helps on the activities choice; strengthen the idea of capacitating to the aged people to make them have autonomy on their choices, participation in the activities where the pedagogical practices actions go beyond the systematized practice of physical education.
Keywords: Programs of physical education; Health promotion and old aged